Farmers' use of agricultural extension communication channels for receiving farm management information in Polokwane Local Municipality, Limpopo Province - Mahlangu, Nelly Nokuthula (My University, 2019)
This study was designed to examine the perceptions of subsistence farmers about the use of the extension communication channels to receive farm management information including climate variability in relation to their innovation decision process. A survey approach was used in this study and by means of stratified sampling, 85 farmers were selected from 372 respondents from Mankweng and 251 from Tshebela service centres in Polokwane Local Municipality for interviews considering gender and their proportions in each service centre. Data were collected from individual respondents by means of personal interviews using a semi-structured questionnaire. The questionnaire was tested among similar farmers in a village near the University of Limpopo. The data were subjected to both descriptive and inferential analyses using the Statistical Package for the Social Sciences (SPSS) programme. The findings around the research questions and the hypothesis test showed that all respondents received farm management information including climate variability through all 10 communication channels investigated. Furthermore, it was indicated that group discussion was the only channel through which most respondents received information most of the time. The study findings also revealed that of all the channels investigated, slightly more than half of the respondents preferred group discussions and of those who preferred group discussions, almost half of them preferred it as the first choice. The hypothesis test further showed that the farmer characteristics that positively influence farmers‟ use of group communication channels were farming experience, farmer association membership and affordability group channels. In other words, a farmer who has more farming experience and belongs to a farmers‟ association is more likely to choose group channels for receiving farm management information including climate variability. The hypothesis test also indicated that the strongest predictor of reporting preference of group channels of communication channels was seeking innovation for a farm management problem in relation to climate variability. Finally, the study found that time was the most serious constraint farmers face in assessing or receiving farm management information including climate variability. ix In view of the fact that most respondents will have group discussions as their first choice, the use of this channel should be timed to allow respondents to attend. Extension agents therefore, have to discuss the timing of such meetings with participants to arrive at times suitable to most participants. Extension agents also need to realise that a subsistence farmer who is looking for information for a farm management problem including climate variability is more likely to seek it through the television.
Thesis (M.A. Agricultural Management (Agricultural Extension)) -- University of Limpopo, 2019
Keywords: Perception; Extension; Group discussion; Climate; Variability; Farm; Management; Innovation; Channel; Communication; Agricultural extension work -- South Africa -- Limpopo; Farm management -- South Africa -- Limpopo; Communication in agriculture